EFFECTIVE PRINCIPLES OF TEACHING WRITING IN EFL CONTEXTS - Mavluda Yusupova (Bright Mind Publishing, 2025)
Writing, as one of the most cognitively demanding language skills, plays a central role in English as a Foreign Language (EFL) contexts. Effective writing instruction in EFL settings demands more than merely correcting errors—it involves guiding learners through recursive processes, engaging genres, promoting autonomy, and integrating sociocultural feedback mechanisms. This theoretical paper synthesizes key principles and pedagogical perspectives from writing research—especially the process approach, genre-based pedagogy, communicative and sociocultural theories, explicit strategy instruction, and feedback/assessment practices. Drawing on seminal works (Hyland, 2003; Raimes, 1983; Graham & Perin, 2007; Bhowmik, 2021) and contemporary empirical studies, the paper proposes a coherent framework for designing writing pedagogy in EFL settings. Recommendations and implications for curriculum design and teacher professional development conclude the discussion.
Keywords: Writing pedagogy, EFL, process approach, genre instruction, feedback, learner autonomy.